Análise da fragilidade potencial e emergente e das condições de sustentabilidade ambiental no Município de Quixeramobim, CE - Amorim, Caroline Domingos de (2023)
Human occupation in natural environments often leads to the occurrence of environmental imbalances. Understanding this interaction is fundamental to comprehend the processes that affect environmental systems, such as degradation and its exposed consequences through impacts and risks. In the face of such a question, the relevance of studying environmental fragility is highlighted, which employs an approach related to the principles of ecodynamics, enabling an integrated analysis of environmental components and the knowledge of fragility levels for specific areas. Thus, it allows an assessment of the potentialities and limitations of the environments, as well as the development of better environmental planning and territorial management. The spatial study area was the municipality of Quixeramobim, Ceará, an area that presents significant changes due to forms of spatial appropriation and lacks research related to this theme. The present research aimed to analyze potential and emerging environmental fragility in the municipality of Quixeramobim, adopting the methodology proposed by Ross (1994), with some adaptations. The following methodological steps were undertaken: bibliographic research, cartographic and remote sensing survey, fieldwork, data classification, data processing, and the evaluation of results, based on criteria used by Souza (2000), relating fragility levels to conditions of environmental sustainability. The results indicated that approximately 34.35% of the municipal territory has Low Potential Fragility (LPF), 25.60% has Medium Potential Fragility (MPF), and 40.06% exhibits High Potential Fragility (HPF). Regarding Emerging Fragility, 28.10% has Low Emerging Fragility (LEF), 44.17% presents Medium Emerging Fragility (MEF), and 27.17% reveals High Emerging Fragility (HEF). It was verified that environmental sustainability decreases as high fragilities are noted. Therefore, the fulfillment and elaboration of environmental policies, public policies, and specific policies, focusing on sustainable development, were considered essential. The lack of sustainable measures can ensure the increase of degradation and consequently of fragility.